2021
DOI: 10.1080/1226508x.2021.1875868
|View full text |Cite
|
Sign up to set email alerts
|

The Macroeconomic Consequences of Stimulating Offline Consumption during COVID-19

Abstract: This paper analyses the macroeconomic consequences of a fiscal policy implemented in South Korea during COVID-19, 'Korean Economic Impact Payment (KEIP)' program, that aims to stimulate offline consumption. In doing so, we modify a SIR-macro model by explicitly distinguishing online-and offline consumption goods. Benchmark analysis predicts that (1) there are positive effects on key macro variables at the impact while progress of the epidemic hardly changes and (2) the transfer multiplier from the KEIP is esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
1
4
0
1
Order By: Relevance
“…The pandemic has destabilized the economic structure of economies coupled with uncertainties in the world. As a result, governments all over the world have put in place stimulus packages to reduce the cascading effects of the pandemic on their economies (Kim et al 2021;Cui et al 2020). History is replete with fiscal measure policymakers instituted to mitigate the impact of past pandemics, which will serve as pointers to the current pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…The pandemic has destabilized the economic structure of economies coupled with uncertainties in the world. As a result, governments all over the world have put in place stimulus packages to reduce the cascading effects of the pandemic on their economies (Kim et al 2021;Cui et al 2020). History is replete with fiscal measure policymakers instituted to mitigate the impact of past pandemics, which will serve as pointers to the current pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have recently stressed the significance of technological advancement and its function in achieving environmental sustainability. Energy use, according to (Deleidi et al 2020), is critical to economic growth, and their findings in their study of the relationship between energy use and economic growth revealed a positive relationship (Kim et al 2021).…”
Section: Technological Progress and Environmental Regulationmentioning
confidence: 99%
“…The GTA is a proactive strategy to combat climate change. Greener manufacturing makes the companies use renewable energy resources that biologically nourish the firm’s FP [ 54 ].…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%